Alkali Activated Slag Mortars Provide High Resistance to Chloride-Induced Corrosion of Steel - Criado, Maria; Provis, John L. (Frontiers in Materials, 2018)
The pore solutions of alkali-activated slag cements and Portland-based cements are very different in terms of their chemical and redox characteristics, particularly due to the high alkalinity and high sulfide content of alkali-activated slag cement. Therefore, differences in corrosion mechanisms of steel elements embedded in these cements could be expected, with important implications for the durability of reinforced concrete elements. This study assesses the corrosion behaviour of steel embedded in alkali-activated blast furnace slag (BFS) mortars exposed to alkaline solution, alkaline chloride-rich solution, water, and standard laboratory conditions, using electrochemical techniques. White Portland cement (WPC) mortars and blended cement mortars (white Portland cement and blast furnace slag) were also tested for comparative purposes. The steel elements embedded in immersed alkali-activated slag mortars presented very negative redox potentials and high apparent corrosion current values; the presence of sulfide reduced the redox potential, and the oxidation of the reduced sulfur-containing species within the cement itself gave an electrochemical signal that classical electrochemical tests for reinforced concrete durability would interpret as being due to steel corrosion processes. However, the actual observed resistance to chloride-induced corrosion was very high, as measured by extraction and characterisation of the steel at the end of a 9-month exposure period, whereas the steel embedded in white Portland cement mortars was significantly damaged under the same conditions.